Occurrence and comprehensive treatment of stress-related neurotic and somatoform disorders in students of different years and specialties - Yurtsenyuk, Olha S. (Psychiatry, Neurology and Medical Psychology, 2020)
Topicality. Importance of current studies dealing with stress-related neurotic and somatoform disorders at a young age is determined by the necessity to find new forms of psychological support directed to social adaptation and harmonious personal development of students.Objective: to investigate occurrence of stress-related neurotic and somatoform disorders in students of different years and specialties, to develop a comprehensive treatment of the above conditions.  Materials and methods. 1235 students underwent a comprehensive check-up during the period from 2015 to 2017 keeping to the principles of bioethics and deontology. The following methods were applied: clinical, clinical-psychopathological, clinical-epidemiological, clinical-anamnestic, experimental-psychological and statistical. Sampling did not differ considerably by the sex and age, place of residence, and form of education. The check-ups were performed in the period between examinations.   Results. Investigation of the systematic sampling resulted in the fact that neurotic stress-related and somatoform disorders were found in 187 (15,14%) students that constituted 58,99% of all the nonpsychotic psychic disorders (NPD) diagnosed in young people. The nosology F 40.0-48.1 was found in 62 (33,16%) men and 125 (66,84%) women. The biggest amount of neurotic stress-related and somatoform disorders was diagnosed in the 1st and 3rd year students: 67,12% and 77,78% respectively (р<0,05). Those students studied on the specialties «General Medicine», «Stomatology», «Practical Psychology». Antidepressants, anxiolytics, anticonvulsive, nootropic agents, vitamins and various kinds of psychotherapy (cognitive-behavioral, systemic family, Gestalt, psychoanalysis, client-centered and body-focused therapy) were applied in the treatment of neurotic stress-related and somatoform disorders.   Conclusions. The obtained results should be considered in making screening diagnostic, therapeutic and preventive measures for the students at higher educational institutions.